2016
DOI: 10.5812/jjm.34867
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Rotavirus and Adenovirus in the Childhood Gastroenteritis

Abstract: Background: Acute gastroenteritis stemming from viral causes is very common during the childhood period. Rotavirus and enteric adenovirus are the most common factors of acute gastroenteritis encountered in infants and children. However, the epidemiology of rotavirus and enteric adenovirus gastroenteritis in the east Anatolia region is not well-known. Objectives: We aimed to evaluate the relationship between the distribution of antigen positivity in rotavirus and enteric adenovirus antigen tests required cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 13 publications
3
14
1
5
Order By: Relevance
“…In Turkey, acute gastroenteritis is a serious public health problem, affecting over 352 000 children younger than 5 years old annually (http://tsim.saglik.gov.tr/tsim). Recent studies have revealed that RVA is responsible for 6‐28% of cases of childhood gastroenteritis . Rotavirus infections in Turkey are most commonly observed between the beginning of September and the end of May, with the highest rates occurring in the first 4 months of the year .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Turkey, acute gastroenteritis is a serious public health problem, affecting over 352 000 children younger than 5 years old annually (http://tsim.saglik.gov.tr/tsim). Recent studies have revealed that RVA is responsible for 6‐28% of cases of childhood gastroenteritis . Rotavirus infections in Turkey are most commonly observed between the beginning of September and the end of May, with the highest rates occurring in the first 4 months of the year .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that RVA is responsible for 6-28% of cases of childhood gastroenteritis. [24][25][26][27][28] Rotavirus infections in Turkey are most commonly observed between the beginning of September and the end of May, with the highest rates occurring in the first 4 months of the year. 9 More than one third of infections occur in children younger than 2 years of age, 9,24 and rates of rotavirus positivity are similar between males and females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high prevalent rate of rotavirus found in this study under 5 years of age may be due to underdeveloped immune system of children, lack of hygienic practices and consumption of raw food and untreated water. In several literatures, rotavirus is considered as the most common cause of viral gastroenteritis [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…play a vital role in causing diarrhoea [5,6]. Rotavirus remains the most common cause of severe diarrhoea and adenovirus causes acute gastroenteritis under the age of 5 years [7,8]. Three forms of diarrhoea (watery diarrhoea, bloody diarrhoea and persistent diarrhoea) are potentially lifethreatening diarrhoea during childhood.…”
Section: Introductionmentioning
confidence: 99%